Evaluation of selective outcome reporting and trial registration practices among addiction clinical trials. (16th January 2020) - Vassar, Matt; Roberts, William; Cooper, Craig M.; Wayant, Cole; Bibens, Michael
Abstract: Background and Aims: Selective outcome reporting occurs when trialists pre‐specify primary and secondary outcomes during trial planning but alter the definitions in the published report. Here, we investigate selective outcome reporting in published addiction randomized controlled trials (RCTs) and evaluate whether particular funding sources are associated with an increased likelihood of selective outcome reporting. Design: We conducted a cross‐sectional study of published addiction clinical trials. A PubMed search was performed to identify RCTs in addiction journals from 2013 to 2017. Included studies used a randomized design to address one of the following topics: (1) drug, alcohol and tobacco addiction prevention, (2) stabilization following excessive use of a substance, (3) relapse prevention or (4) recovery maintenance. Setting: Single‐center, medical research institution. Participants: Our sample included 162 RCTs that were prospectively registered with a clearly defined primary outcome. Measurement: We extracted the following items from addiction RCTs: journal, funding source, trial registry number (if included), sample size, dates of subject enrollment, whether primary and secondary outcomes were denoted, all published outcomes, P‐ value for all outcomes and whether authors mentioned any deviations from the trial protocol as it related to RCT outcomes. Findings: In total, 47 of 162 RCTs (29.0%) had at least one major discrepancy between the trial registry and published RCT. Overall, these 47 RCTs included 54 major discrepancies. The most common major discrepancy was demotion of a primary registered outcome (19/54, 35.2%). The majority of RCTs (132/162, 81.5%) were funded from public sources. Additionally, 166 RCTs were excluded from our sample because registration could not be confirmed. Conclusions: There is evidence suggestive of selective outcome reporting in addiction randomized controlled trials (RCTs). The most common major discrepancies pertained to the primary outcome.